AYURVEDIC MANAGEMENT OF CHRONIC KIDNEY DISEASE –A CASE STUDY (AYUSHDHARA, 2017)
The term Chronic Renal Failure applies to the process of continuing significant irreversible reduction in nephron number. In present scenario the cost of dialysis can’t be afforded by every patient and understanding this by means of principles explained in Ayurveda is necessary to manage the disease & make the patient comfortable to perform his daily routine. CKD patients treated with Ayurveda may prolong dialysis or reduce its frequency, it also maintains the stage without further damage. Various recipes of Ayurveda are reported to be effective for CRF kidney failure and goal is to provide with a better drug formula. In this study, Bakayan Swaras, Ksheerpaka of Ashvagandha, Shatavari and Gokshura churna, Syrup Neeri KFT, Shiva Gutika are found to be quite effective in management of chronic renal failure. Here we are reporting a case of CKD of a 41 year old female patient who was given some Ayurvedic preparations. The drug under consideration is effective in increasing the gap between two successive dialysis cycles in few patients but as the sample size was very small no concluding statement can be given in this regards meanwhile  trial drug (Melia azedarach) can be used as adjuvant therapy in patients of chronic renal failure along with other treatment modalities.